Complete Morris Syndrome. Case Presentation - Manyeles Brito Vázquez; Ángela Belkis Brito García; Delvis Batista García (Revista Finlay)
Androgen insensitivity syndrome, Morris syndrome or testicular feminization is a disorder in sexual differentiation, in which the individual is phenotypically feminine, but with a man's genetic characteristics. The case of a 9-year-old schoolgirl with bilateral inguinal hernia is presented as a form of presentation of Morris syndrome. It is assessed in consultation confirming the presence of testicles in the surgery, corroborated by pathological anatomy. A karyotype was described describing chromosomally 46XY. In prepubertal age it is reevaluated with bilateral inguinal hernias and external genitals of female appearance. It is verified by imaging examinations, the absence of uterine body and annexes, with presence of permeable vagina until its middle third, which ends in a blind sac inside the pelvis, performing orchiectomy by minimal access without vaginoplasty. Bilateral inguinal hernia in childhood was the form of presentation of Morris syndrome in this patient. The case is presented due to the low frequency of occurrence of this condition.